Management of directive leadership and teaching performance in the I.E. N ° 3089 "Los Angeles" - Window. Lima 2018 - Vidal Gonzales, Ofelia (2018)
The scientific research we have done is basic, non-experimental causal correlation, the study factors are two: Management Leadership and evaluation of teaching performance in Educational Institution No. 3089 "Los Angeles" - Ventanilla. Lima 2017. The population is made up of 4 Directors and 200 Teachers and the sample is made up of 4 Directors and 132 Teachers. The research design is transactional, correlational, causal. bivariate, transversal. Two questionnaires were drawn up for data collection: one for the directive leadership variable and the other for a variable teacher performance evaluation, which was applied to the sample. The instruments comply with the qualities of validity and reliability. The study proposes the following research hypothesis: The Directive Leadership significantly influences the evaluation of the teaching performance in the Educational Institution. The results obtained allow us to reject the null hypothesis and accept the hypotheses investigated since it was found in a nonparametric test, therefore Kruskal-Wallis test was applied to observe the significant influence between pedagogical leadership and teaching performance with a level of significance of 95% obtaining a value of 0.00, in addition the linear regression test was applied and it was obtained that the pedagogical leadership influences in 42.4% on the teaching performance therefore the null hypothesis is rejected and the alternative hypothesis is accepted research.